Cancer and disease diagnosis - biosensor as potential diagnostic tool for biomarker detection - Chaudhry, Gul-e-Saba; Md. Akim, Abdah; Safda, Naila; Yasmin, Azra; begum, Shaheen; Yeong, Yik Sung; Tengku Muhammad, Tengku Sifzizul (Wolters Kluwer - Medknow, 2022)
Analysis of cancer biomarkers has enormous promise for advancing our molecular understanding of illness and facilitating more precise and timely diagnosis and follow-up care. MicroRNA, exosomes, ctDNA, CTCs, and proteins are only some of the circulating biomarkers that can be detected by liquid biopsy instead of the more intrusive and time-consuming process of doing a tissue biopsy. As the cancer diagnosis bio-markers reveal ultra-low levels in the early stages of the disease, highly sensitive approaches are urgently required. Researchers have taken an interest in a optical biosensor for detecting cancer biomarkers as a potential tool for early disease diagnosis. These techniques have the potential to aid in the development of effective treatments, ultimately leading to a higher rate of patient survival. This review briefly discuss the i) understanding of cancer and biomarkers for early diagonosis purpose ii) Molecular methods and ii) biosensor-based diagnostics. The reseach primary focus on advancement in biosensor design using various concepts ie., Electrochemical, Chemiluminescence and Colorimetric, Surface plasmons (SP), Surface plasmon resonance (SPR), localized surface plasmon resonance (LSPR), Fluorescence, Fiber-based sensors, Terahertz based biosensors, and Surface enhanced Raman spectroscopy (SERS). As a result of the local electric field amplification around plasmonic (usually gold and silver) nanostructures, surface-enhanced Raman spectroscopy (SERS) has emerged as a rapid, selective, and sensitive alternative to conventional laboratory analytical methods, making significant strides in a number of biosensing applications but still under developing stage to be used as diagnostic tool in clinical research.